The Role of Spiritual Practices in Enhancing Well-Being of Cancer Patients: A Phenomenological Study in Ibadan - Oyebanji Israel Temitope; Ogunbiyi David Oluwabukunmi; Oyunwola Taiwo Olayinka (Darul Yasin Al Sys, 2026)
Although cancer care is often dominated by biomedical treatment, the psychosocial and existential dimensions of patients’ experiences remain critical to health outcomes and quality of life. This study examines the impact of spiritual practices on health outcomes and quality of life among cancer patients in Ibadan, Nigeria, with particular attention to coping mechanisms, religiously shaped health perceptions, and the integration of spiritual care within clinical practice. Addressing a gap in culturally relevant and patient-centred cancer care models in Nigeria, the study employed a phenomenological approach involving 20 purposively selected patients. The findings show that spiritual practices function as important frameworks for meaning-making, emotional support, and enhanced self-efficacy, thereby strengthening patients’ resilience and capacity to cope with illness. At the same time, variations across Christianity, Islam, and African Traditional Religions, together with experiences of spiritual struggle and inadequate institutional support, reveal the complexity of integrating spiritual care into oncology settings. The study concludes that spiritual care can substantially enhance holistic well-being when it is aligned with patients’ beliefs and contexts. This research contributes to the development of more culturally adaptive and holistic cancer care by underscoring the need for spiritual care training for healthcare providers, collaboration with religious leaders, and the design of context-sensitive interventions that harmonize medical and spiritual support.